PERBANDINGAN METODE EKSTRAKSI MASERASI DAN SOKLETASI TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN JAMBU BOL (Syzygium malaccense L.) - Henny Nurhasnawati; Sukarmi Sukarmi; Fitri Handayani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Malay apple (Syzygium malaccense L.) is a plant that can be used for treatment. Antioxidants have the activity to reduce free radical compounds which is one of the causes of the emergence of various diseases in humans. The purpose of this study to determine the comparison of methods of maceration and socletation extraction of antioxidant activity of malay apple leaf. Research stages include sampling, plant determination, making of simplisia, maceration extraction and socletation with 70% ethanol solvent and determine the antioxidant activity by UV-Vis spectrophotometry with DPPH (1,1-diphenyl-2-picrylhydrazyl) as free radical. The parameter is IC50 value that is the concentration of antioxidant compound which can cause 50% loss of DPPH free radical activity. Although both methods show very strong antioxidant activity, it can be concluded that the difference in extraction methods has an effect on the antioxidant activity produced. The results of antioxidant activity test showed that socletation methods gave an average IC50 value of 37.67 ppm, this value is higher than maceration methods with an average IC50 value of 47.80 ppm. Malay apple leaf has the potential as a natural antioxidant, although it has a lower IC50 value than vitamin C which is 9.72 ppm.